2016
DOI: 10.1158/0008-5472.can-16-0186
|View full text |Cite
|
Sign up to set email alerts
|

The BRCA1-Δ11q Alternative Splice Isoform Bypasses Germline Mutations and Promotes Therapeutic Resistance to PARP Inhibition and Cisplatin

Abstract: Breast and ovarian cancer patients harboring BRCA1/2 germline mutations have clinically benefitted from therapy with PARP inhibitor (PARPi) or platinum compounds, but acquired resistance limits clinical impact. In this study, we investigated the impact of mutations on BRCA1 isoform expression and therapeutic response. Cancer cell lines and tumors harboring mutations in exon 11 of BRCA1 express a BRCA1-Δ11q splice variant lacking the majority of exon 11. The introduction of frameshift mutations to exon 11 resul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
231
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 227 publications
(240 citation statements)
references
References 47 publications
9
231
0
Order By: Relevance
“…Malignancies often demonstrate loss of heterozygosity, where the wild-type allele is lost but the mutant allele remains present. The ability of BRCA1 mutant alleles to generate protein products that contribute to biological processes normally undertaken by wild-type BRCA1 are beginning to emerge, and although mutant proteins lack tum or-suppressor activity, several truncated BRCA1 protein isoforms have been shown to promote residual DNA repair and chemotherapy resistance (Drost et al, 2011, 2016; Johnson et al, 2013; Shakya et al, 2011; Wang et al, 2016a, 2016b). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malignancies often demonstrate loss of heterozygosity, where the wild-type allele is lost but the mutant allele remains present. The ability of BRCA1 mutant alleles to generate protein products that contribute to biological processes normally undertaken by wild-type BRCA1 are beginning to emerge, and although mutant proteins lack tum or-suppressor activity, several truncated BRCA1 protein isoforms have been shown to promote residual DNA repair and chemotherapy resistance (Drost et al, 2011, 2016; Johnson et al, 2013; Shakya et al, 2011; Wang et al, 2016a, 2016b). …”
Section: Introductionmentioning
confidence: 99%
“…We and others have shown that HR and PARPi resistance can occur when BRCA1 -mutation-carrying alleles produce truncated proteins that are capable of promoting RAD51 foci formation (Drost et al, 2016; Johnson et al, 2013; Wang et al, 2016a, 2016b). Furthermore, previous studies demonstrating 53bp1-KO-induced rescue of embryonic viability utilized Brca1 Δ11 and Brca1 Δ2 alleles that have been shown to produce exon-11-deficient and RING-domain-deficient hypomorphic Brca1 proteins (Bunting et al, 2010, 2012; Cao et al, 2009; Li et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, BRCA1 activity can be salvaged via the use of alternative sites for translation or alternative splicing, which result in the skipping of the affected exon. 21,22 Acquired platinum resistance can be also mediated by the inactivation of TP53BP1 gene encoding for TP53 binding protein 1 as well as by the drug efflux. 5 Combination of cisplatin and mitomycin C provided somewhat more encouraging results when compared with retrospective series of BRCA1-associated OC patients (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Human tumors and cell lines with truncating mutations in exon 11, as well as normal cells, express a related splice variant, BRCA1-Δ11q, resulting from partial skipping of exon 11 (Wang et al 2016a). However, this variant is not in cells with truncating mutations downstream of exon 11.…”
Section: Mechanisms Of Resistance To Poly(adp-ribose) Polymerase Imentioning
confidence: 99%